1995
DOI: 10.1111/j.1532-5415.1995.tb05565.x
|View full text |Cite
|
Sign up to set email alerts
|

A Follow‐Up Study of Age‐Associated Memory Impairment: Neuropsychological Predictors of Dementia

Abstract: The study suggests that, in general, AAMI is nonprogressive, but the AAMI population also includes subjects with early dementia and subjects without genuine memory loss. However, these subjects can be differentiated with a more detailed neuropsychological evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
92
2
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(101 citation statements)
references
References 49 publications
4
92
2
3
Order By: Relevance
“…Different diagnostic criteria have been proposed to distinguish individuals with mild cognitive disorders associated with ageing from non-affected individuals, and one of the best established of these classifications is age-associated memory impairment (AAMI) 1 . AAMI, however, is generally non-progressive and is thus more likely to be a phenomenon of normal ageing 2,3 . The terms 'age-related cognitive decline' (ARCD) and 'ageing-associated cognitive decline' have recently been proposed 4,5 to indicate an objective decline in cognitive functioning associated with the ageing process but within normal limits given the person's age.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different diagnostic criteria have been proposed to distinguish individuals with mild cognitive disorders associated with ageing from non-affected individuals, and one of the best established of these classifications is age-associated memory impairment (AAMI) 1 . AAMI, however, is generally non-progressive and is thus more likely to be a phenomenon of normal ageing 2,3 . The terms 'age-related cognitive decline' (ARCD) and 'ageing-associated cognitive decline' have recently been proposed 4,5 to indicate an objective decline in cognitive functioning associated with the ageing process but within normal limits given the person's age.…”
mentioning
confidence: 99%
“…The terms 'age-related cognitive decline' (ARCD) and 'ageing-associated cognitive decline' have recently been proposed 4,5 to indicate an objective decline in cognitive functioning associated with the ageing process but within normal limits given the person's age. Whether ARCD is the expression of a normal ageing process, or represents a distinct clinical entity or, eventually, a continuum with dementia, is still difficult to establish 2,6 . In fact, recent results from longitudinal studies suggest that the subgroup at high risk for developing dementia may be identified by using a more detailed procedure for the assessment of cognitive decline than those listed in the AAMI criteria.…”
mentioning
confidence: 99%
“…11 3 If there are subjective memory complaints but not objective memory loss and the individual is less than age 80, there is a low risk of either having or developing dementia over a 3.5 year follow-up. 19 The Folstein MMSE is the most commonly used screening test, with a cut-off point of below 24/30 considered by Folstein to be highly suggestive of the presence of dementia. However, such a cut-off point has a low sensitivity and there may be "false positives" with the MMSE.…”
Section: Mental Status Testing and Neuropsychological Screeningmentioning
confidence: 99%
“…Progression rates for AAMI are substantially lower. 19 In a large sample with a mean age of 77, Hogan and Ebly 19a found that, depending on which definition and criteria were used, the percentage surviving with dementia at five years follow-up varied from 21% (for AAMI) to 51% (for MCI criteria). This compares with a dementia prevalence of 14% for those judged "normal" cognitively five years earlier.…”
mentioning
confidence: 99%
“…Seu arcabouço teórico fundamenta-se numa revisão de literatura (Berg et al, 1984;Bondi et al, 1984;Fuld et al 1990;Tuokko et al, 1991;Welsh et al, 1992;Flicker et al, 1993;Masur et al, 1994;Jacobs et al, 1995;Hanninen et al, 1995;Tierney et al, 1996;Grober e Kawas, 1997;Howieson et al, 1997;Kluger et al, 1999;Petersen et al, 1999;Chen et al, 2000) objetivando abranger os domínios cognitivos associados a maior predição para DA: habilidades visuo-espaciais funções executivas, linguagem, recordação imediata e tardia.…”
Section: Descrição Do Cans-mciunclassified